Pengaruh Minat dan Motivasi Belajar Terhadap Hasil Belajar Matematika Siswa Kelas VIII SMP Negeri 11 Mataram - Yulinar Maulinda Dewi; Ketut Sarjana; Junaidi Junaidi; Syahrul Azmi (Griya Journal of Mathematics Education and Application, 2021)
In the 2013 curriculum teachers are required to use diverse learning strategies so that students' learning outcomes improve, but during the math learning process, students' attention is still lacking, and have no interest in the subject. The purpose of this research is to find out the influence of learning interest, and motivation on the results of learning mathematics subjects grade VIII SMP Negeri 11 Mataram Year Lesson 2020/2021. The research method used is the Questionnaire and Documentation Method, which is used to obtain data in accordance with respondents' opinions related to information about learning interests and learning motivation, as well as collecting UAS grades of grade VIII students of SMPN 11 Mataram odd semester of the 2020/2021 school year, which is then processed with descriptive statistics and simple linear regression. The results showed that there is a significant influence on the interest of learning on the results of learning mathematics, There is a significant influence on the motivation of learning on the results of learning mathematics, and there is a significant influence on the interest and motivation of learning on the results of learning mathematics students grade VIII SMP Negeri 11 Mataram School Year 2020/2021.